Identification of a Heme Activation Site on the MD-2/TLR4 Complex - Belcher, John D.; Zhang, Ping; Nguyen, Julia; Kiser, Zachary M.; Nath, Karl A.; Hu, Jianjun; Trent, John O.; Vercellotti, Gregory M. (Frontiers in Immunology, 2020)
Myeloid differentiation factor-2 (MD-2) binds lipopolysaccharide (LPS) and initiates toll-like receptor-4 (TLR4) pro-inflammatory signaling. Heme also activates TLR4 signaling, but it is unknown if heme interacts with MD-2. Therefore, we examined MD-2 for a potential heme activation site. Heme-agarose and biotin-heme/streptavidin-agarose pulled down recombinant MD-2, which was inhibited by excess free heme. UV/visible spectroscopy confirmed MD-2-heme binding. To determine whether MD-2 was required for heme-mediated TLR4 signaling, HEK293 cells were transfected with MD-2, TLR4, CD14 and an NF-κB luciferase reporter, and then stimulated with heme or LPS. Heme or LPS treatment elicited robust reporter activity. Absence of MD-2, TLR4 or CD14 plasmid abolished NF-κB reporter responses to heme or LPS. In silico analysis identified two potential heme docking sites on MD-2 near conserved amino acids W23/S33/Y34 and Y36/C37/I44. Heme-induced NF-κB activity was reduced by 39% and 78% in HEK293 cells transfected with MD-2 mutants W23A and Y34A, respectively, compared to WT-MD-2. NF-κB activation by LPS was not affected by the same mutants. Biotinyl-heme/streptavidin-agarose pulled down 68% less W23A and 80% less W23A/S33A/Y34A mutant MD-2 than WT-MD-2. In contrast, at the Y36/C37/I44 MD-2 site, heme-induced NF-κB activity was significantly increased by mutants Y36A (191% of WT-MD-2) and unchanged by mutants C37A and I44A (95% and 92%, respectively, of WT-MD-2). In conclusion, these data suggest that heme binds and activates TLR4 signaling at amino acids W23 and Y34 on MD-2.